Training To Improve The Skills Of Youth Posyandu Cadres In Preventing Anemia And Stunting With Balanced Nutrition In The Tunjuk Village, Tabanan District - Ida Ayu Eka Padmiari; Pande Putu Sri Sugiani (CV. AFDIFAL MAJU BERKAH, 2024)
In adolescent girls, the need for iron increases because they experience regular menstruation/menstruation which releases a certain amount of iron every month. The increase in the need for total blood volume is often not followed by adequate iron consumption, especially when entering adolescence, girls tend to want to have a slimmer body, so they often make various efforts, including going on a strict diet. Based on data from the 2022 Indonesian Nutritional Status Survey (SSGI), the prevalence of Stunting in Toddlers in Tabanan Regency is still above the prevalence of Stunting in Bali Province (8.0%) while Tabanan Regency is 8.2%. With the nutritional counseling that has been carried out, it has not been enough to increase knowledge and especially the attitudes of adolescents towards the risk factors for stunting, therefore the community service will conduct a Skills Improvement Training for Adolescent Posyandu Cadres in preventing Anemia and Stunting with Balanced Nutrition in Tunjuk Village, Tabanan District. The prioritized solution is to carry out Skills Improvement Training for Adolescent Posyandu Cadres in preventing Anemia and Stunting with Balanced Nutrition in Tunjuk Village, Tabanan District by providing training. The method used to achieve the objectives of this community service is to carry out training which is carried out for 2 days on 50 adolescent Posyandu Cadres. This community service activity was carried out in Tunjuk Village, Tabanan District, Tabanan Regency from July to October 2024. There was a significant increase in the knowledge, attitudes and skills of adolescent posyandu cadres in preventing anemia and Stunting with Balanced Nutrition.